Pemberdayaan Perempuan Kepala Keluarga (PEKKA) dalam Meningkatkan Ekonomi Keluarga oleh Dinas Pemberdayaan Perempuan Perlindungan Anak Dan Keluarga Berencana (DP3AKB) Di Desa Menampu Kecamatan Gumukmas Kabupaten Jember - Najmiyah Yizil Ulal Yaqini; Febrina Rizky Agustina (Jurnal Al-Tatwir, 2023)
PEKKA (Perempuan Kepala Keluarga) means a woman or a widow who becomes the sole provider in the household, especially in terms of financial needs. Naturally this is not easy for many of these sole providers since many of them come from low economic levels and educational backgrounds. The women empowerment programme carried out by DP3AKB through the PEKKA empowerment programme is carried out to produce women with potential and high enthusiasm so that the knowledge and experience gained can become the basic capital to improve the economy of the families. The current qualitative descriptive research aims to identify and describe the process of PEKKA empowerment programme in improving the family economy by DP3AKB, describing the supporting factors, inhibiting factors and impacts of PEKKA empowerment programme in improving the family economy by DP3AKB in Menampu Village, Gumukmas District, Jember Regency. The results of the research indicate that DP3AKB collaborates with the government of Menampu Village along with KUA Gumukmas counselors to empower PEKKA by providing socialization processes, guidance, and training, as well as conducting intensive efforts to ensure that the knowledge obtained can support a mindset that forms more independent behavior and can develop the potential of PEKKA to support changes in their lives.